Optimized supply chain model reduces health system costs in DRC. Issue 30 (5th July 2021) - Thomas, Dorothy; Motomoke, Eomba; Crawford, Jessica; Defawe, Olivier; Makaya, Archimede; Ngwato, Jean Willy; Bompongo, Joel; Monzembela, Jose; Ailstock, Gabriella; Bancroft, Emily; Magadzire, Bvudzai; Baabo, Dominique; et al.
Highlights: After implementing optimized model, we observed 34% reduction in supply chain costs. Costs increased for Provincial store but decreased for Zones and health facilities. Streamlined distribution practices supported cost reductions for transportation. After implementing optimized model, costs increased in control Zones and facilities. Abstract: Objective: In 2017, an optimized immunization supply chain (iSC) model was implemented in Equateur Province, Democratic Republic of the Congo. The optimized model aimed to address iSC challenges and featured direct deliveries to service delivery points (SDPs), longer replenishment intervals and increased cold chain capacity. This assessment examines iSC costs before and 5 months after implementing the optimized model. Materials & Methods: We used a nonexperimental pre-post study design to compare iSC costs before and after implementation. We applied an activity-based costing approach with a comparison arm to assess procurement, management, storage and transportation costs for three iSC tiers: Province (n = 1); Zone (n = 4) and SDP (n = 15). We included data from 3 treatment Zones and 11 treatment SDPs; 1 control Zone and 4 control SDPs. We used sample and population data to estimate iSC costs for the entirety of Equateur Province. Results: In the period immediately before implementing the optimized model, estimated annual iSC costs were $974, 237. Following implementation, estimated annual iSC costs were $642, 627—a 34% ($331, 610) reduction. This change in costs was influenced by a 43% ($180, 313) reduction in SDP costs, a 67% ($198, 092) reduction in Zonal costs and an 18% ($46, 795) increase in Provincial costs. After implementing the optimized model, average iSC costs for treatment Zones was $6, 895 (SD: $6, 072); for the control Zone was $21, 738; for treatment SDPs was $989 (SD: $969); and for control SDPs was $1, 356 (SD: $1, 062). Conclusions: We observed an absolute reduction in iSC costs in treatment Zones while control Zone post-implementation iSC costs remained the same or increased. The greatest cost reductions were for storage and transport at Zones and SDPs. Although cost implications of this model must continue to be evaluated over time, these findings are promising and will inform decisions around project expansion.